Nonprofits as "Schools of Democracy": A Comparative Case Study of Two Environmental Organizations. (June 2016) - Dodge, Jennifer; Ospina, Sonia M.
This article presents a comparative case study of two nonprofit organizations that do community organizing in the environmental field and asks how do nonprofits school citizens in democracy? Although the literature suggests the importance of social capital, a practice approach surfaces important political dimensions that have not been sufficiently explored. We find that distinct organizational practices create contexts for participants to exercise specific ways of being and doing—called "subject positions"—vis-à-vis the state and their political community. These practices support member participation by serving to construct "citizens"—rather than customers or clients—who develop skills in critical thinking and who exercise agency in the organization and the policy field they seek to influence. These practices represent key mechanisms for schooling citizens in democracy in these nonprofit organizations and link participation in the organization with broader political participation. We discuss implications for theory and practice.